Vom Paradigma der Guten Form. Deutsch-deutsche Geschmackserziehung und Kontinuitätskonstruktion(en) - Ochs, Amelie (Artium Quaestiones, 2021)
Beginning with the Bauhaus anniversary in 2019, new perspectives are being revealed on GDR design. This promises a revision of the German design historiography of the last decades, which was dominated by West-German perspectives. Referring to this trend in research, my essay questions the German history and historiography of design. After the Second World War, the German historiography of art followed the paradigm of the Cold War (Abstraction in the West, Socialist Realism in the East). The historiography of design followed this schema by distinguishing “socialist” from “capitalist” design. To this day, this prevents “transnational” perspectives. In contrast to this, I agree with the argument that the consolidation of the two German states occurred with reference to the (old) concept of “good form”, among other things. Even though the different discourses refer to similar objects and references, they are structured by different interpretations of the term “Good Form”, referring to the ruling ideology of the particular state. It represents a central argument in aesthetic education (Geschmackserziehung), which contained moral and political values. In 1950s West Germany, the Deutscher Werkbund, an organization which was involved in processes of institutionalization in both the political and design historical field, was the main driver of this discourse. In contrast to this, the institutionalization of design in the GDR was organized by the state. Nevertheless, distinctive parallels in the discourses in East and West suggest the lasting impact of the Werkbund. Consequently, I argue that the discursive foundations, which were laid in the 1950s at the latest, had a lasting influence on “German-German” (deutsch-deutsch) design historiography and have recently opened up a pan-German (gesamtdeutsch) perspective.